Konsep dan Falsafah Teknologi Pendidikan - Emilia Emilia; Nur Azizah; Muhammad Rifky Azmi (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2023)
Educational technology appears to be an issue along with the development of human life and the need for education and learning. Improving educational technology as a science and profession is determined by the region and field of work. The field of work develops, implements, proves and improves theory based on input from the field. The concept of educational technology in a narrow sense can be an educational medium, namely the result of technology as a tool in education so that it is effective, efficient and effective. The philosophy of educational technology is the study and ethical practice of facilitating learning and enhancing performance by creating, using, and managing appropriate technological processes and resources. Through systematic efforts in identifying, developing, organizing, and utilizing various learning resources as well as managing the entire process.